Assessment of Professional Counseling Dispositions: A Content Validity Analysis - Patrick R Mullen; Jacob Joseph; Kaitlin Jones Hinchey; Morgan Walker; Jennifer Niles (Teaching and Supervision in Counseling, 2024)
Counselor educators evaluate the professional counseling dispositions of trainees throughout their development within training programs. There have been few consistent articulations of professional dispositions as many programs and measures define them differently. In our study, we developed the Assessment of Professional Counseling Dispositions (APCD) and performed a content validity study of the measure. Our findings provide evidence for the content validity of the APCD. We discuss these findings, their implications, and future research using the measure.
Keywords: professional dispositions; content validity; counseling; assessment